Formulation of floating metronidazole microbeads using Terminalia mantaly gum as polymer - Tolulope Omolola Ajala; Olorundara T Moshood; Oluwatoyin Adepeju Odeku (University of Huddersfield Press, 2021)
The aim of the present study was to evaluate Terminalia mantaly gum as a polymerin the formulation of floating metronidazole microbeads. Terminalia gum was extracted and characterized by material, proximate and pasting properties. Terminalia gum in combination with sodium alginate at varying concentrations (0-80%w/v) was used in preparing the microbeads by ionotropic gelation using zinc chloride as the chelating agent. The microbeads were evaluated using shape, size, swelling, buoyancy, entrapment efficiency, drug release profiles and kinetic modelling. The microbeads were spherical to ovoid in shape with sizes ranging from 1093 to 1209.0 µm. The swelling index was 5 to 184 % and it increased with an increase in gum concentration. Total floating time was highest(175.5 h) for formulations having 20% w/w gum and the least(5.5 h) for those with 80% w/w gum. The entrapment efficiency generally increased with an increase in gum concentration up to 40% w/w and then reduced. The microbeads showed controlled release patterns of metronidazole with the highest t50 of 2260.3. The drug release kinetics fitted the Korsmeyer-Peppas model with a non-Fickian anomalous diffusion mechanism. Terminalia mantaly gum can be further developed for use as a co-polymer in the formulation of floating metronidazole microbeads.